The Novelty of Inventions Owned by Vietnamese Higher Education Institutions - Van Hai, Tran (VNU Journal of Science: Policy and Management Studies; Vol 40 No 3DO - 10.25073/2588-1116/vnupam.4515, 2024)
Higher education institutions simultaneously perform the functions of education and scientific research, including basic and applied research. Inventions are one of the outcomes of applied research. Statistics show that during the period from 2019 to 2023: - Vietnamese higher education institutions were granted 141 invention patents out of 779 invention registration applications submitted, with a protection rate of 18.10%; - Vietnamese higher education institutions were granted 205 utility solution patents out of 496 utility solution registration applications submitted, with a protection rate of 41.33% (the lowest in both quantity and protection rate compared to individuals, enterprises, and research institutes). The article analyzes the inventions deemed to lack novelty, the main reasons for the refusal of patent protection for inventions from Vietnamese higher education institutions, and proposes solutions to improve the patent protection rate for these institutions.